CHEMICAL COMPOSITION OF NA’MATAK AND ITS MEDICINAL PROPERTIES (International journal of medical sciences, 2026)
Dog rose (Rosa canina L.) is notable for its chemical composition and medicinal properties. This article reviews the main biologically active substances of dog rose, including carotenoids, flavonoids, vitamins and minerals, polyphenols, and unsaturated fatty acids. The medicinal properties of the plant include its antioxidant, antimicrobial, anti-inflammatory, and antiradical effects. The high antioxidant properties of dog rose, as well as its beneficial effects on the cardiovascular system, gastrointestinal system, and immune system, have been scientifically proven. The article presents a scientific analysis aimed at assessing the medicinal potential of dog rose.